IMPLEMENTASI MODERASI BERAGAMA DAN TANTANGAN KEBERAGAMAN DI SEKOLAH: TINJAUN KEPUSTAKAAN DALAM PEMBELAJARAN PAI - Wahyuni, Sri; Ramadhan, Putri Utami (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
The religious diversity present in Indonesia is very vulnerable to the emergence of religious conflicts. Therefore, a formulation is needed that can be used to prevent the occurrence of religious conflicts. This research aims to provide understanding through literature from various sources, so that it can serve as a reference for educators to design lessons that are integrated with the values of religious moderation. The method used in the preparation of the research is literature study with content analysis. Research results indicate that the internalization of religious moderation values can be carried out through several approaches, both those directly related to classroom learning, such as integrating them with subject matter that has been packaged in the curriculum, and classroom habituation, as well as other activities outside of classroom learning, such as collaborating with stakeholders and providing learning facilities that support the practice of applying religious moderation.